Kaempferol and Isorhamnetin alleviate Lipopolysaccharide-Induced Anxiety and Depression-Like Behavioral in Balb/C Mice - Ekici, M; Güngör, H; Mert, DG (Journal of the Hellenic Veterinary Medical Society, 2023)
The etiology of anxiety and depression is linked to inflammation and oxidative stress. Isorhamnetin and Kaempferol are strong antioxidants with antiinflammatory and neuroprotective properties. This study, it was aimed to investigate the effect of Kaempferol and Isorhamnetin in Lipopolysaccharide (LPS)-induced anxiety and depression model in mice. Thirty Balb/C mice were divided into six groups of five mice each weighing 25-35 gr. Kaempferol (50 mg/kg and 100 mg/kg) and Isorhamnetin (30 mg/kg and 60 mg/kg) were given orally to the treatment group, and the vehicle was given to the control and LPS groups for fourteen days, followed by intraperitoneal (0.83 mg/kg) LPS injection (control group excluding) on the fifteenth day. Kaempferol and Isorhamnetin ameliorated LPS-induced anxiety evaluated by open field test, light/dark test, and elevated plus maze test, and LPS-induced depression evaluated by forced swimming test and tail suspension test. Kaempferol and Isorhamnetin alleviated LPS-induced increased oxidative stress in the prefrontal cortex and hippocampus by decreasing MDA and total oxidant status (TOS) levels and increased total antioxidant status (TAS) levels. In addition, it was observed that Kaempferol and Isorhamnetin regulated the increase in prefrontal and hippocampal inflammation caused by LPS by decreasing TNF-α, IL-1β, and IL-6 levels. Most importantly, LPS reduced prefrontal and hippocampal brain-derived neurotrophic factor (BDNF) levels, but the treatment groups reversed it. These results show the possible therapeutic potential of Kaempferol and Isorhamnetin, along with the importance of oxidative stress, inflammation, and BDNF in the etiopathogenesis of anxiety and depression.